Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1104/pp.80.1.52
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of N Nutrition on the Water Relations and Gas Exchange Characteristics of Wheat (Triticum aestivum L.)

Abstract: The purpose of this study was to characterize leaf photosynthetic and stomatal responses of wheat (Triticum aestivum L.) plants grown under two N-nutritional regimes. High-and low-N regimes were imposed on growth-chamber-grown plants by fertilizing with nutrient solutions containing 12 or I millimolar nitrogen, respectively. Gas-exchange measurements indicated not only greater photosynthetic capacity of high-N plants under well-watered conditions, but also a greater sensitivity of CO2 exchange rate and leaf co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 22 publications
(28 reference statements)
6
45
1
1
Order By: Relevance
“…The lower shoot DW with N, NP and NPK fertilization may be due to an increase in assimilate allocation to roots for maintaining root growth, for osmotic adjustment and for turgor maintenance [10,25,26]. Similar results were reported by other authors [21,47,48]. Therefore, higher root/shoot ratios could be exploited as a strategy for stress tolerance in crop plants.…”
Section: Discussionsupporting
confidence: 76%
“…The lower shoot DW with N, NP and NPK fertilization may be due to an increase in assimilate allocation to roots for maintaining root growth, for osmotic adjustment and for turgor maintenance [10,25,26]. Similar results were reported by other authors [21,47,48]. Therefore, higher root/shoot ratios could be exploited as a strategy for stress tolerance in crop plants.…”
Section: Discussionsupporting
confidence: 76%
“…The objective of this research was to assess the effects of nitrogen fertilisation, with three different doses, on the water relations of tomato plants exposed to drought with the same water deficit regardless the original size of the plants, in order to clearly separate, in accordance with Morgan (1986), the intrinsic effects of N-nutrition from those related to plant growth phenomena, and to assess comparable water-stress regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Osmotic adjustment of 0.49 MPa (average in three cultivars) was evident at the highest N level in the water stress treatment. Morgan (1986) observed an osmotic adjustment of 0.29 MPa with higher N supply under water stress in wheat. Increase in osmotic adjustment with increasing N levels was largest in P-3358, smallest in G-4578, and intermediate in FFR-677, and this cultivar order was the same as that of the reduction in injury percentage in the PEG test under water stress conditions.…”
Section: Resultsmentioning
confidence: 91%
“…Plants were stressed by limited soil moisture at higher N levels. Decreases in leaf water potential with higher N levels and low soil moisture conditions have been observed in various crop plants (Radin and Parker 1979;Radin and Ackerson 1981;Morgan 1986). Radin et al (1982) observed decreases in the leaf water potential of about 0.4 MPa with higher N level in cotton.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation